Enhancing Competitiveness in Vocational Education: The Role of Strategic Marketing in Schools - Zainul, Mohammad (JURNAL AL-TANZIM, 2024)
This study aims to analyze marketing strategies to improve vocational high school competitiveness in Indonesia. This study uses a qualitative approach with a case study type. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis is done through data reduction, presentation, and conclusion. The study results indicate that the school's competitive advantage lies in its special expertise in automotive technology, strong partnerships with leading companies, and modern facilities. The school's proactive approach to updating its curriculum to suit industry needs, effective branding and digital media strategies, and partnerships with industry have contributed to its success in producing employable graduates. The implications of this study suggest that vocational schools can improve their competitiveness by adopting a strategic marketing approach that focuses on building strong industry partnerships, developing relevant curricula, and utilizing digital media to promote their vocational programs.